The Motivation Effect on Barista Performance: (Case Study on Hungrypedia Serang) - Prayogi, Ichsan Adil; Malik, Abdul; Marthalena, Marthalena; Santi, Endang Tri (Indonesian Journal of Social Science Research, 2025)
This research discusses how motivation can affect the performance of an employee serving coffee, or better known as a barista. This research uses Clayton Alderfer's ERG (Existence, Relatedness, & Growth) theory. This research uses descriptive qualitative research methods, which aim to provide a comprehensive and in-depth view of the subject under study, namely the influence of motivation on barista performance. By taking the locus of a coffee shop, the author tries to analyze how barista motivation can affect work motivation. The results of the research in this article show that work motivation is very influential on the performance of the barista, with work motivation, the barista will have more confidence in working. Existence Needs, Relationship Needs, and Growth Needs have a significant effect on barista performance. The influence of the motivation and performance of the barista in the coffee shop is that the presence of work motivation makes the barista more enthusiastic about work, and later it will have a good impact on work and will later get rewards in the form of existence, growth, and good relations with relationships. The need for growth is the main factor for the resource person to become a barista at Hungrypedia Serang Cafe